Achieving Steady and Stable Energy from AlGaAsGaAs Solar Cells - Sojoudi, M.; Madatov, R.; Sojoudi, T.; Farhadi, P. (Engineering, technology & applied science research, 2011)
The hetero junction operating as a solar cell is based on n GaAs p GaAs p Al0.75Ga0.25As. This paper investigates the influence of radiation electron ray on layers of hetero-junction AlGaAsGaAs. Long term operation in the radiation zone degrades solar cell power operating parameters and reduces overall cell’s life. The impact of radiation electron ray has been analyzed with various doses on layers of the AlGaAsGaAs hetero junction. V-A characteristics and parameters such as the photocurrent density (Jsc), voltage at open circuit (Voc) and energy conversion efficiency ( (η), are evaluated for different doses of electron radiations. It is shown that current and voltage decrease when irradiation doses increase. Further, Jsc and η parameters decrease proportionally to the increase of the electron radiation doses whereas Voc is only slightly decreased.